Imagination and Literary Forms in of Orfi Shirazy Poems - یدالله بهمنی; مهران شادی (مطالعات زبانی و بلاغی)
Orphi Shirazi is a powerful and visionary poet of 10th (Hijri) who initiated the circulation of a new style in Persian poetry. This poet who has a sharp vision and a creative mind was successful both in creation of new matters and innovation of new combinations and images. Orphi form his creation of content with very initiative skillfulness and use of imagination as well as figures of speech. In this article we try to, by analyzing Orphi`s poems, consider some of his principal level of language with a stylish view and analyze them form the point of view of imagination and figures of speech. To this effect we tried to consider orphi`s frequent imagination and figures of speech which have, stylish values through exact analysis of Orphi`s odes examples. In this research distinctions of Orphi`s poems are also analyzed from the point of view of imagination and figures of speech. The main reference of this study is orphi`s poems which are the basis of our analysis. Experts` points of views are also considered in this study.